A qualidade de serviços como diferencial competitivo em concessionárias de automóveis - Manzoni, Cesar Adolar Soares (2010)
This paper presents a case study in a car dealership, located in Rio Grande do Sul, Brazil. We aimed to examine the strategic management of services and identify factors such as competitive advantage to customer loyalty in a car dealership. To achieve this goal it was necessary at first, perform a search of the literature on service quality and, subsequently, analyze the survey of satisfaction with sales and delivery of new vehicles and a satisfaction survey with technical assistance services, both performed by the manufacturer. Subsequently, we identified which of the perception of the utility in relation to the five dimensions of quality, both for satisfaction with sales, and for satisfaction with the service. Following, was built from the macro auto dealership, where they identified six business processes, being the most important business process of selling new cars. To obtain a deeper knowledge about the process of selling new cars, was made its mapping and prepared the flow chart of the same. Produced after the cycle of service, where we observed the moments of truth in the process of selling new cars. The mapping of subprocess in preparation for delivery of new vehicles is also part of this work, because it is a continuation of the sale, being considered the grand finale. To collect the data was used documents and unstructured interviews, applied to the sales team, which identified the problems that cause more stress and rush to the team before the time of delivery of the vehicle. From that we attempted to identify the possible causes, through the use of cause and effect diagram 4M, and possible solutions. This analysis allowed us to elaborate the plan of action 5W1H, and use the method Pokayoke, as a preventive way for the occurrence of faults. Customer loyalty is directly related to their satisfaction, since only very satisfied customers have earned their loyalty. One way to achieve this high level of satisfaction is through the quality of services rendered flawlessly, as well as the quality of care.